Perbandingan Efektivitas Zat Pengatur Tumbuh Organik dan Anorganik dalam Mendukung Pertumbuhan Stek Kopi Robusta - Rudi Hartawan; Yulistiati Nengsih; Khairul Purba; Aditya Deska Wahyu (Universitas Batanghari, 2023)
Robusta coffee plants are cross-pollinated, so the genetic characteristics of the new plant are not the same as the parent if propagation is carried out generatively. One way to overcome this problem is through vegetative propagation. The research aims to determine the effectiveness of organic and inorganic growth regulators to support the growth of robusta coffee cuttings. This research was conducted at the Experimental Station, Campus II, Batanghari University in Pijoan, Jambi from April to August 2022. The research used a completely randomized environmental design. The treatment design is 5 levels of organic and inorganic growth regulators, namely (p0): control, (p1): 50% onion shallot extract, (p2): natrium nitrophenol 0.60 mLL-1, (p3): 75% onion shallot extract, (p4): natrium nitrophenol 0.90 mLL-1. The parameters observed were live cuttings, rooted cuttings, sprouted cuttings, rooted and sprouted cuttings, number of roots, dry weight of roots, air temperature and air humidity. Research data was processed using anova. Further data processing takes the form of orthogonal contrast to compare organic and inorganic growth regulators. A onion shallot extract concentration of 75% is better than a concentration of 50% and a natrium nitrophenol concentration of 0.9 mLL-1 is better than a concentration of 0.6 mLL-1. Treatment with 75% onion shallot extract resulted in 100% growing cuttings, 100% sprouting cuttings, 60.22% rooted cuttings, and 60.22% sprouting and rooting cuttings. Natrium nitrophenol treatment with a concentration of 0.9 mLL-1 resulted in 100% growing cuttings, 100% sprouting cuttings, 65.55% rooted cuttings, and 65.55% sprouting and rooting cuttings. Organic growth regulators from onion shallot extract and inorganic substances from natrium nitrophenol have the same effect in stimulating the growth of robusta coffee cuttings.